2023
DOI: 10.3390/ani13050869
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fecal Microbiota Communities between Primiparous and Multiparous Cows during Non-Pregnancy and Pregnancy

Abstract: Imbalances in the gut microbiota composition may lead to several reproductive disorders and diseases during pregnancy. This study investigates the fecal microbiome composition between primiparous and multiparous cows during non-pregnancy and pregnancy to analyze the host-microbial balance at different stages. The fecal samples obtained from six cows before their first pregnancy (BG), six cows during their first pregnancy (FT), six open cows with more than three lactations (DCNP), and six pregnant cows with mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Age-dependent changes in microbial compositions affecting the alpha diversity are also seen in the gut of humans [21], and are generally attributed to the diversity of the microbiota of the mother of the newborn fetus. In the analysis of fecal microbiota of primiparous and multiparous cows, it was also found that the fecal microbiota α diversity of primiparous cows was higher than that of multiparous cows [22]. P-H had a larger relative abundance of Firmicutes and Bacteroidetes and lower abundance of Proteobacteria than MP-H, consistent with previous earlier investigations [23].…”
Section: Discussionsupporting
confidence: 88%
“…Age-dependent changes in microbial compositions affecting the alpha diversity are also seen in the gut of humans [21], and are generally attributed to the diversity of the microbiota of the mother of the newborn fetus. In the analysis of fecal microbiota of primiparous and multiparous cows, it was also found that the fecal microbiota α diversity of primiparous cows was higher than that of multiparous cows [22]. P-H had a larger relative abundance of Firmicutes and Bacteroidetes and lower abundance of Proteobacteria than MP-H, consistent with previous earlier investigations [23].…”
Section: Discussionsupporting
confidence: 88%
“…Compared with parturient sows, the differences in the gut microbiome of first-parity sows may be related to energy metabolism. A study showed a higher relative abundance of Methanobrevibacter and a lower relative abundance of Rikenellaceae_RC9_gut_group and dgA-11_gut_group in the gut microbiota of multiparous cows compared to primiparous cows [ 26 ]. These alterations in the most representative taxa might be associated with the host’s energy metabolism [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed a higher relative abundance of Methanobrevibacter and a lower relative abundance of Rikenellaceae_RC9_gut_group and dgA-11_gut_group in the gut microbiota of multiparous cows compared to primiparous cows [ 26 ]. These alterations in the most representative taxa might be associated with the host’s energy metabolism [ 26 ]. The changes observed in the gut microbiota of primiparous sows might be associated with the challenge they encounter in distributing nutrients to support maternal growth, in addition to fulfilling the needs of fetal growth and lactation [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%